The special strength and its effect on the completion of the javelin throw for beginners Experimental research (Journal of the College of Basic Education, 2023)
The second half of the twentieth century was marked by a global revolution that swept across all fields.life, and scientific development was able during this period of time to find solutions to manyMisconceptions that have been dominant in many areas of human life, as well as manyof the problems he suffered from for many years, and it is worth noting that this development has reachedThe level of human incapacitation in some sports such as athletics and gymnastics.It has been proven beyond any doubt that the digital level of the various activities has jumped.To the imam in a way that raises questions and debates. Where are the limits of human capacity? What are the real reasons behind this development?To answer such questions, quite a few specialists haveAnd researchers to study these reasons, as the answer was limited to several factors, namely readinessThe personal profile of the player in terms of anthropometric and morphological aspects, as well as the level of physical fitness.the special force, in addition to the effectiveness of the training plan used and the extent ofIt is based on the scientific method, and there are factors that have proven their influence and effectiveness as a method.Nutrition, lifestyle and others.There is no doubt that each of the aforementioned factors has an important role in raising the digital level of development.With regard to the throwing activities, especially the javelin throwing event, it depends mainly onon the level of special physical fitness for this event, specifically the element of special strength, and does not implyThat is neglecting the other factors, the javelin throwing event is one of the activities that needrequirements of high accuracy and need physical confrontations with special specifications, and the most important of these